Re-design Corporate Identity Wanda Electronic - Juwita Wirta Sri Depi; Jamilus .; Syafwandi . (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Abstrack Target and benefit of this re-design is (1) to differentiate Wanda Electronic with shop of electronic other (2) so that can be recognized broaderly by consumer (3) also become expense place of electronic searched by society.This scheme use model of prosedural having the character of is descriptive, scheme process which is the prosedural orient to increase the effort Marwan. Formulation of problem and identify and also the target of intake of data pass/through the way of observation, interview and documentation laterthen in analysis and finally become concept of scheme. Result of this device later will wear to promote better Wanda Electronic so that again consumer eye and make its effort much more go forward from at now. Keywords : Re-design, logo, identitas, Wanda Elektronic.